Employee Perception on the Role of HR for Creating and Managing Employer Branding towards its Brand:An Explorative Study - Dash, Srinibash; Mohapatra, J. (Prabandhan: Indian Journal of Management, 2016)
Employer brand is the image of your organization as an employer and how it is related to employees. Your employer value proposition (EVP) communicates that image to your target audience(s) and reinforces why talented people would want to join (and stay with) your organization. In the same way, it has been stated that it represents the organization as an employer and how this employer relates to its employees, not just the current employees, but potential employees as well. It is about branding and positioning the organization as an employer-as a great place to work. In this context, it is said that employer branding is a very complex concept. An employer brand is the expression of corporate culture and the corporate brand. Therefore, it will be a challenge to clearly isolate the factors of communication from other factors such as leadership, organizational structure, and other communication as well as personnel management. Hence, depending on the organizational structure, there might be different cultures within an organization. The size and organizational influence of each department will then also play a role. A big question is also where employer branding is driven in the organization and how it is supported by top management with a positive perception in the employees' minds.